NAFLD: CV Risk Regardless of Hyperglycemia or Obesity - Buckley, Rita (MD Conference Express, 2011)
The prevalence of nonalcoholic fatty liver disease (NAFLD) has been estimated to be between 20% and 30% in the general population, but this value is much higher (approximately 70% to 80%) in individuals with type 2 diabetes. Increasing recognition of NAFLD and its strong relationship with metabolic syndrome has stimulated an interest in its possible role in the development of cardiovascular disease [Targher G et al. Diabetologia 2008].